In and out of anorexia : the story of the client, the therapist, and the process of recovery - Ronen, Tammie (Counseling and psychotherapy transcripts, client narratives, and reference works., 2001)
Interleaving the stories of therapist and client, this is a positive and helpful book for people with anorexia and those who care for them. Ayelet describes her experiences of this life-threatening illness, her repeated hospitalizations and eventual successful recovery, and includes examples of drawing and writing made when she was ill. Her therapist outlines the progress of the cognitive constructivist therapy and the rationale behind her decisions and treatment considerations. Also included are an overview of current research into anorexia and its treatment and a glossary of key terms that make this book a comprehensive as well as inspiring resource.